Categorie discrete e percezioni continue: per un lessico delle nuove migrazioni - Di Salvo, Margherita (Italian Canadiana, 2024)
This article investigates 20 qualitative interviews collected with new migrants of Italian origins settled in Toronto (Ontario) and in London (UK). The aim of the study is to identify the identity markers used by migrants to express their feeling of belonging to Italy and to Canada/UK and to position themselves into two different categories, expat and migrants. According to previous quantitative studies, these two labels refer to two different patterns of immigration: expat in fact includes contemporary skilled and temporary migrations, while migrant deals with unskilled migrations. So, the study of identity markers used in qualitative interviews is crucial in order to investigate how migrants position themselves in the host Country.The results provide evidence of a deep distinction of two different groups of speakers: the first one is composed of those Italians who consider themselves as expats and this is evident since they report in their interviews all those identity markers discussed in the literature as typical of this kind of migration (level of education, social status, use of English). The second one is, instead, composed of those Italians who consider themselves as migrants using those markers already reported in the bibliography for migrants (and not for expats, such as the poor use of English, the low level of education and the temporary job).